The disease-resistance gene Pto and the fenthion-sensitivity gene fen encode closely related functional protein kinases. - Loh, Y T (1995)
Resistance to bacterial speck in tomato is governed by a gene-for-gene interaction in which a single resistance locus (Pto) in the plant responds to the expression of a specific avirulence gene (avrPto) in the pathogen. Disease susceptibility results if either Pto or avrPto are lacking from the corresponding organisms. Leaves of tomato cultivars that contain the Pto locus also exhibit a hypersensitive-like response upon exposure to an organophosphorous insecticide, fenthion. Recently, the Pto gene was isolated by a map-based cloning approach and was shown to be a member of a clustered multigene family with similarity to various protein-serine/threonine kinases. Another member of this family, termed Fen, was found to confer sensitivity to fenthion. The Pto protein shares 80% identity (87% similarity) with Fen. Here, Pto and Fen are shown to be functional protein kinases that probably participate in the same signal transduction pathway.